Phase Equilibrium Data Study With Carbon Dioxide Solvent For 80.52:19.48 Of Ethanoloctane Mixture At Elevated Pressure. - Davarnejad, R; A, Suhairi; Sata, Sata; Zainal, A.; Kassim, K. M. (2008)
Solubility data of a mixture containing 80.52 % ethanol and 19.48 % octane was measured in carbon dioxide solvent using a high-pressure type phase equilibrium apparatus at pressures up to 100 bar and at temperature of 75 °C. The experimental results showed that considerable separation was not achieved in this ethanol and octane ratio using carbon dioxide.